Penyelesaian Sengketa Wansprestasi Melalui Mekanisme Arbitrase - Ade Maulana; Devi Siti Hamzah Marpuang (Program Studi Hukum Universitas Pamulang, 2021)
Wansprestasi is the implementation of obligations that are not fulfilled or broken promises or even do something that according to the agreement cannot be done. Default gives legal consequences to the party who did it and brings consequences to the emergence of the right of the injured party to sue the party who did the default to provide compensation, so that by law it is hoped that neither party will be harmed because of the negligence made by the debtor either because they do not carry out what has been promised or default. Arbitration is a way of resolving a civil dispute outside the general court based on an arbitration agreement made in writing by the disputing parties. Basically, this is in accordance with the provisions stated in Article 7 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (Law 30/1999) which reads in full as, The parties can agree on a dispute that occurs or that will occur between them to be resolved by arbitration. the agreement to resolve a dispute through arbitration is contained in a document signed by the parties, the arbitration agreement is an agreement in the form of an arbitration clause stated in a written agreement made by the parties before the dispute arises, or a separate arbitration agreement made by the parties after it arises. disputes mentioned (Article 1 point 3 of Law 30/1999).